2012
DOI: 10.1002/app.38434
|View full text |Cite
|
Sign up to set email alerts
|

Effect of compatibilizing agents on the mechanical properties of high‐density polyethylene/olive husk flour composites

Abstract: International audienceThe main objective of this research was to investigate the effect on the thermal and mechanical properties of the addition of two different compatibilizing agents, malefic anhydride-grafted polyethylene (PE) [synthesized in a solution state (MAPE) and commercial (XA255)], to olive husk flour, high-density polyethylene (HDPE) composites. The composites contain 30 wt % of olive husk flour and a variable proportion of compatibilizer (3, 5, and 7 wt %). The grafting reaction was followed by F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 22 publications
4
18
0
Order By: Relevance
“…We registered the appears of two new absorption bands of average intensity around 1779 cm −1 and 1715 cm −1 , which corresponded to the vibrations of elongation of the carbonyls groups C=O of MAH. The first peak was assigned to the grafted anhydride, which was due to symmetric (strong) and asymmetric (weak) C=O stretching vibration of succinic anhydride rings grafted on the PE backbone, respectively . The second peak was assigned to the grafted maleic acid formed from ring‐opening reaction of the succinic anhydride because of moisture .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We registered the appears of two new absorption bands of average intensity around 1779 cm −1 and 1715 cm −1 , which corresponded to the vibrations of elongation of the carbonyls groups C=O of MAH. The first peak was assigned to the grafted anhydride, which was due to symmetric (strong) and asymmetric (weak) C=O stretching vibration of succinic anhydride rings grafted on the PE backbone, respectively . The second peak was assigned to the grafted maleic acid formed from ring‐opening reaction of the succinic anhydride because of moisture .…”
Section: Resultsmentioning
confidence: 99%
“…However, most of conventional thermoplastics containing polyethylene (PE), polypropylene (PP), and polyvinyl chloride (PVC) were hydrophobic while the natural fillers were hydrophilic . Therefore, solving the incompatibility between hydrophobic thermoplastics and hydrophilic natural fillers was crucial for improving performance of WPC, especially when the fillers content increased above 50 wt % .…”
Section: Introductionmentioning
confidence: 99%
“…Given the chemical composition of this residue, mainly lignin, hemicellulose and cellulose, different strategies have been developed for its exploitation, being the most common its incineration for energy generation [11]. Nonetheless, alternative uses of agricultural wastes, such as their exploitation as a sustainable reinforcement for composites, are regarded as potentially important within the field of materials technology [12][13][14][15]. In fact, polypropylene (PP) ground olive stone residue (OSF) reinforced composite are expected to show high stiffness values, due to the high hardness of the olive stones.…”
Section: Introductionmentioning
confidence: 99%
“…The solid waste can be burned to produce electric energy or heat, or turned into activated carbon after a thermal treatment for the removal of poisonous metals from water . The possible use of the solid by‐products as a source of compost material has also been approached . The conversion of olive stone flour (OSF) into viscous polyols, likely to be used in polyurethane foams, was successfully accomplished by total and partial oxypropylation .…”
Section: Introductionmentioning
confidence: 99%
“…Despite the considerable amount of solid waste generated by olive oil extraction, to the best of our knowledge, only a few research works reported in the literature have tackled the use of olive stones as fillers in polymer‐based composite materials. Using the search term “olive stone,” “olive kernel,” or “olive pit” and composites, only eight English scientific publications have been reported by ISI since 1993, six of which were devoted to thermoplastic matrix . Among these reported research works, only two were concerned with polyvinyl chloride (PVC) as a polymer matrix .…”
Section: Introductionmentioning
confidence: 99%